Evaluation of electrical and photovoltaic behaviours as comparative of Au/n-GaAs (MS) diodes with and without pure and graphene (Gr)-doped polyvinyl alcohol (PVA) interfacial layer under dark and illuminated conditions - Tecimer, H. Uslu; Altindal, Şemsetti̇n; Cicek, O.; Uslu, I.; Tecimer, H.; Tan, S. O. (Elsevier BV, 2016)
Abstract Au/n-GaAs (MS) type Schottky diodes (SDs) were fabricated with and without pure and Gr-doped PVA interlayer to evaluate the effects of Gr-doped PVA interlayer on the basic electrical parameters (i.e. saturation current (Io), ideality factor (n), barrier height (ФBo), series (Rs) and shunt resistances (Rsh) both under dark and illuminated conditions (50–200 W), at room temperature. Using different calculation methods (i.e. thermionic emission (TE) model, Ohm's Law and Norde's method), these parameters were obtained from the current-voltage (I-V) data and compared with each other in various conditions. In our research, it is clear that there are a decrease in Rs value and an increase in Rsh value for Gr-doped PVA in comparison with the pure PVA structure under dark and illuminated conditions, therefore rectifier rate (RR = IF/IR), is the proof of the quality for diodes, significantly improved. Also, the ΦBo values with interlayer (pure and Gr-doped PVA) are lower than without. Consequently, these results indicate that the PVA (pure and Gr-doped) changed effectively the BH according to other structure and, moreover, Gr-doped PVA layer significantly improved the quality of Au/PVA/n-GaAs structure under dark and illuminated conditions.
Keywords: 7. Clean energy